Determinants of protests: Longitudinal evidence from Ukraine's Orange Revolution - Carlos Bozzoli; Tilman Brück (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper is the first study that analyzes the drivers of political protest using longitudinal data from a critical revolution that changed -at least temporarily- the political landscape in a transition country. We make use of a rich dataset consisting of panel data collected before and after the so called Orange revolution in Ukraine. Our empirical approach tackles two different -and equally interesting- features of the revolution: the determinants of participation (both in the protests and counter-protests) and the selection of participants into different levels of involvement (i.e. intensity of participation). We consider different drivers of participation, from traditional proxies for opportunities and grievances, but we also analyze the role of political and economic preferences, risk tolerance, life satisfaction, and indicators of network connectivity. What emerges from this study is a more nuanced pattern of participation that does not link uniquely to a single theoretical model.
Keywords: P20; D74; 330; conflict; protest; transition economy; Ukraine; longitudinal studies; Soziale Bewegung; Partizipation; Übergangswirtschaft; Ukraine